Interoceptive pathways to understand and treat mental health conditions - Nord, Camilla L.; Garfinkel, Sarah N. (Trends in cognitive sciences, 2022)
An increasing recognition that brain and body are dynamically coupled has enriched our scientific understanding of mental health conditions. Peripheral signals interact centrally to influence how we think and feel, generating our sense of the internal condition of the body, a process known as interoception. Disruptions to this interoceptive system may contribute to clinical conditions, including anxiety, depression, and psychosis. After reviewing the nature of interoceptive disturbances in mental health conditions, this review focuses on interoceptive pathways of existing and putative mental health treatments. Emerging clinical interventions may target novel peripheral treatment mechanisms. Future treatment development requires forward- and back-translation to uncover and target specific interoceptive processes in mental health to elucidate their efficacy relative to interventions targeting other factors. Patients with neuropsychiatric disorders associated with altered emotional or physical experiences show disruptions in interoception.Interoception may be an important target of both existing and novel mental health treatments.Antidepressants modulate aspects of interoception and specific psychological therapies target interoceptive processes, particularly breathing.Medications for certain physical health conditions are associated with better mental health.Interoceptive measures could be used to stratify patients for treatment selection.